Early Effects of Cyclophosphamide, Methotrexate, and 5-Fluorouracil on Neuronal Morphology and Hippocampal-Dependent Behavior in a Murine Model. (25th October 2019) - Anderson, Julie E; Trujillo, Madison; McElroy, Taylor; Groves, Thomas; Alexander, Tyler; Kiffer, Frederico; Allen, Antiño R
Abstract: Breast cancer (BC) is the most common cancer among women. Fortunately, BC survival rates have increased because the implementation of adjuvant chemotherapy leading to a growing population of survivors. However, chemotherapy-induced cognitive impairments (CICIs) affect up to 75% of BC survivors and may be driven by inflammation and oxidative stress. Chemotherapy-induced cognitive impairments can persist 20 years and hinder survivors' quality of life. To identify early effects of CMF administration in mice, we chose to evaluate adult female mice at 2-week postchemotherapy. Mice received weekly IP administration of CMF (or saline) for 4 weeks, completed behavioral testing, and were sacrificed 2 weeks following their final CMF injection. Behavioral results indicated long-term memory (LTM) impairments postchemotherapy, but did not reveal short-term memory deficits. Dendritic morphology and spine data found increases in overall spine density within CA1 basal and CA3 basal dendrites, but no changes in DG, CA1 apical, or CA3 apical dendrites. Further analysis revealed decreases in arborization across the hippocampus (DG, CA1 apical and basal, CA3 apical and basal). These physiological changes within the hippocampus correlate with our behavioral data indicating LTM impairments following CMF administration in female mice 2-week postchemotherapy. Hippocampal cytokine analysis identified decreases in IL-1α, IL-1β, IL-3, IL-10, and TNF-α levels.